Outer Membrane Vesicles Derived from Adherent-Invasive Escherichia coli Induce Inflammatory Response and Alter the Gene Expression of Junction-Associated Proteins in Human Intestinal Epithelial Cells - Bahareh Nadalian; Banafsheh Nadalian; Mohammad Reza Zali; Abbas Yadegar (Canadian Journal of Infectious Diseases and Medical Microbiology)
Adherent-invasive Escherichia coli (AIEC) pathobionts, which are characterized by their ability to adhere to and invade intestinal epithelial cells, are associated with the etiopathogenesis of inflammatory bowel diseases (IBDs). Outer membrane vesicles (OMVs) released by AIEC strains can facilitate the interaction of these bacteria with host cells through delivering bacterial effectors. The aim of this study was to determine the ability of OMVs derived from AIEC strain LF82 to induce the host immune response, leading to production of proinflammatory cytokines and also altering the gene expression of junction-associated proteins in the human epithelial colorectal adenocarcinoma Caco-2 cell line. OMVs were extracted from AIEC strain LF82, and the cell viability of Caco-2 cells treated with these vesicles was assessed by MTT assay. The morphology and size distribution of vesicles were analyzed using transmission electron microscopy and dynamic light scattering, respectively. Gene expression of occludin, ZO-1, claudin-2, E-cadherin, TLR-2, and TLR-4 in response to OMVs was assessed in Caco-2 cells by RT-qPCR. Moreover, the secretion of IL-8 and TNF-α into the supernatant of Caco-2 cells upon treatment with OMVs was measured using ELISA. Our results demonstrated that OMVs upregulated the gene expression level of TLRs and also altered the gene expression level of junction-associated proteins. OMVs derived from AIEC may play a major role in the promotion of intestinal inflammation and epithelial barrier dysfunction. However, further investigations are needed to elucidate the putative role of OMVs in the pathogenesis of AIEC and IBD.